2016
DOI: 10.5194/acp-16-6241-2016
|View full text |Cite
|
Sign up to set email alerts
|

Fast descent routes from within or near the stratosphere to the surface at Fukuoka, Japan, studied using <sup>7</sup>Be measurements and trajectory calculations

Abstract: Abstract. By using high concentrations of 7Be as an indicator, we clarify fast descent routes from within or near the stratosphere to Earth's surface, with the study site being in Fukuoka, Japan. Most routes arise from high latitudes through the following processes. First, the descent associated with a tropopause fold occurs, followed by southward movement with slow descent at the rear side of a strong trough. Because this motion occurs along an isentropic surface, the descending air parcels nearly conserve th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Figures a–d show the mean height of the back trajectories when high values (higher than the 75th percentile) of 7 Be, 7 Be/ 210 Pb, and O 3 (the same analysis for 210 Pb is reported in the supporting information) are registered at CMN. This analysis clearly shows that high‐altitude back trajectories originating in the lower stratosphere come from the Arctic (where the tropopause is also lower due to limited convective overturning) and North America/Atlantic regions, with special strength over Greenland, whereas the lowest trajectories are coming from the lowest‐latitude regions, in agreement with Itoh and Narazaki []. It is found that high 7 Be/ 210 Pb values always match the top height in the back trajectories, pointing out once more the importance of the 7 Be/ 210 Pb activity ratio as a tracer of vertical motions in connection with STE events.…”
Section: Resultssupporting
confidence: 82%
“…Figures a–d show the mean height of the back trajectories when high values (higher than the 75th percentile) of 7 Be, 7 Be/ 210 Pb, and O 3 (the same analysis for 210 Pb is reported in the supporting information) are registered at CMN. This analysis clearly shows that high‐altitude back trajectories originating in the lower stratosphere come from the Arctic (where the tropopause is also lower due to limited convective overturning) and North America/Atlantic regions, with special strength over Greenland, whereas the lowest trajectories are coming from the lowest‐latitude regions, in agreement with Itoh and Narazaki []. It is found that high 7 Be/ 210 Pb values always match the top height in the back trajectories, pointing out once more the importance of the 7 Be/ 210 Pb activity ratio as a tracer of vertical motions in connection with STE events.…”
Section: Resultssupporting
confidence: 82%
“…The global model simulation assuming the tripling of Asian anthropogenic emissions from 1985 to 2010 indicated an increase in O 3 mixing ratios by 2-6 ppbv in the western US and by 1-3 ppbv in the eastern US on a monthly mean ba-sis, with the maximum effect occurring during April-June; this increase was suggested to more than offset the benefits of 25 % domestic reduction in the western US (Jacob et al, 1999). Based on the Emission Database for Global Atmospheric Research (EDGAR) version 4.3.1, anthropogenic emissions of NO x and VOCs in China are estimated to have increased by 3.2 and 2.1 times during 1985, respectively (Crippa et al, 2016, which is generally consistent with the assumption by Jacob et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the direct connection between STT and peaks in groundlevel O 3 observations are generally infrequent, with only a small fraction of STT trajectories descending below the mid-troposphere (Viezee et al, 1983;Derwent et al, 1998;Eisele et al, 1999;Stohl, 2001;Škerlak et al, 2014). Air from the free troposphere is largely limited to daytime entrainment into the lowest layer of the atmosphere as the planetary boundary layer (PBL) height increases (e.g., Itoh and Narazaki, 2016;Ott et al, 2016); however, the ability for O 3 -rich air to reach the surface depends on a complex array of factors including the diurnal cycle (Itoh and Narazaki, 2016;Langford et al, 2009Langford et al, , 2012Ott et al, 2016) and the seasonal cycle of the PBL height (Langford et al, , 2017, the presence of convective mixing (Thompson et al, 1994;Eisele et al, 1999;Langford et al, 2017), and the elevation of the monitoring station, which if located within the free troposphere, especially with the nighttime collapse of the PBL, can experience direct STT (Langford et al, , 2017. The influence of the stratospheric air, although weaker by the time the air reaches the surface (Monks, 2000), can last longer in the mid-to lower troposphere if the O 3 -rich air becomes entrained in high-pressure systems behind the surface cold front and continues to subside (Danielsen, 1980;Davies and Schuepbach, 1994;Cooper et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%